2013
DOI: 10.1614/wt-d-12-00069.1
|View full text |Cite
|
Sign up to set email alerts
|

Weed Management Strategies to Reduce Herbicide Use in Zero-Till Rice–Wheat Cropping Systems of the Indo-Gangetic Plains

Abstract: In the rice–wheat (RW) systems of the Indo-Gangetic Plains of South Asia, conservation tillage practices, including zero-tillage (ZT), are being promoted to address emerging problems such as (1) shortages of labor and water, (2) declining factor productivity, (3) deterioration of soil health, and (4) climate change. Despite multiple benefits of ZT, weed control remains a major challenge to adoption, resulting in more dependence on herbicides for weed control. Alternative management strategies are needed to red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
83
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(90 citation statements)
references
References 68 publications
(108 reference statements)
5
83
1
1
Order By: Relevance
“…Rice residue management in no-till systems (surface retention) provides multiple benefits, including soil moisture conservation, suppression of weeds, improvement in soil quality (Balwinder-Singh et al 2011a, Ram et al 2013Kumar et al 2013;Singh et al 2005;Verhulst et al 2011), reduction in greenhouse gas emissions equivalent to nearly 13 t ha -1 (Mandal et al 2004), and regulates canopy temperature at the grain-filling stage to mitigate the terminal heat effects in wheat (Gupta et al 2010;Jat et al 2009), and significantly improves the C sustainability index (Jat et al 2011). The suppression of weeds with straw mulch might help reduce herbicide requirements (Yadvinder-Singh et al 2010b).…”
Section: Y Singh and H S Sidhumentioning
confidence: 99%
“…Rice residue management in no-till systems (surface retention) provides multiple benefits, including soil moisture conservation, suppression of weeds, improvement in soil quality (Balwinder-Singh et al 2011a, Ram et al 2013Kumar et al 2013;Singh et al 2005;Verhulst et al 2011), reduction in greenhouse gas emissions equivalent to nearly 13 t ha -1 (Mandal et al 2004), and regulates canopy temperature at the grain-filling stage to mitigate the terminal heat effects in wheat (Gupta et al 2010;Jat et al 2009), and significantly improves the C sustainability index (Jat et al 2011). The suppression of weeds with straw mulch might help reduce herbicide requirements (Yadvinder-Singh et al 2010b).…”
Section: Y Singh and H S Sidhumentioning
confidence: 99%
“…For example, Kumar et al (2013) present data demonstrating that combinations of rice (Oryza sativa L.) residue and early wheat (Triticum aestivum L.) planting dates substantially reduced emergence of littleseed canarygrass. They also highlight breeding efforts aimed at improving weed-suppressive traits in both rice and wheat.…”
mentioning
confidence: 93%
“…], and littleseed canarygrass (Phalaris minor Retz.) (Kumar et al 2013). A more mechanistic understanding of how integration of multiple nonchemical weed management tactics impact these problematic species will be helpful for the long-term viability of low-input and organic reduced tillage crop production.…”
mentioning
confidence: 99%
“…In those soybean areas under no-tillage where buttonweed is a difficult-to-control weed, the increase in straw amount on the soil surface has the potential to reduce buttonweed emergence and consequently, its establishment, avoiding subsequent interference with the crop. For instance, a study on rice under no-tillage showed that 5,000 kg ha −1 of superficial wheat straw reduced weed density from 22 to 76 % and promoted predation of rice-wheat weeds (Kumar et al, 2013). Other studies have also shown that weed suppression was species-specific and could be achieved with residue from different plant species being present on the soil surface (Campiglia et al, 2012;Mirsky et al, 2013;Anderson, 2014).…”
Section: Resultsmentioning
confidence: 99%